High phenylalanine concentrations induce demyelination and microglial activation in mouse cerebellar organotypic slices - Thau-Zuchman, Orli; Pallier, Patrick N.; Savelkoul, Paul J. M.; Kuipers, Almar A. M.; Verkuyl, J. Martin; Michael-Titus, Adina T. (Frontiers in Neuroscience, 2022)
Phenylketonuria (PKU) is an inborn error of metabolism. Mutations in the enzyme phenylalanine hydroxylase (PAH)-encoding gene lead to a decreased metabolism of the amino acid phenylalanine (Phe). The deficiency in PAH increases Phe levels in blood and brain. Accumulation of Phe can lead to delayed development, psychiatric problems and cognitive impairment. White matter (WM) damage is a neuropathological hallmark of PKU and can be seen even in early-detected and treated PKU patients. The mechanisms linking high Phe concentrations to WM abnormalities remain unclear. We tested the effects of high Phe concentrations on myelin in three in vitro models of increasing complexity: two simple cell culture models and one model that preserves local brain tissue architecture, a cerebellar organotypic slice culture prepared from postnatal day (P) 8 CD-1 mice. Various Phe concentrations (0.1 to 10 mM) and durations of exposure were tested. We found no toxic effect of high Phe in the cell culture models. On the contrary, the treatment promoted the maturation of oligodendrocytes, particularly at the highest, non-physiological Phe concentrations. Exposure of cerebellar organotypic slices to 2.4 mM Phe for 21 days in vitro (DIV), but not 7 or 10 DIV, resulted in a significant decrease in myelin basic protein (MBP), calbindin-stained neurites, and neurites co-stained with MBP. Following exposure to a toxic concentration of Phe, a switch to the control medium for 7 days did not lead to remyelination, while very active remyelination was seen in slices following demyelination with lysolecithin. An enhanced number of microglia, displaying an activated type morphology, was seen after exposure of the slices to 2.4 mM Phe for 10 or 21 DIV. The results suggest that prolonged exposure to high Phe concentrations can induce microglial activation preceding significant disruption of myelin.